2017
DOI: 10.1021/acs.jpcc.7b08864
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Mechanism of Water Molecules on the PuO2(110) Surface: An Ab Initio Molecular Dynamics Study

Abstract: Reactions between water and plutonium oxide play a key role in determining the oxidation and corrosion rates of plutonium materials. We perform consecutive ab initio molecular dynamics simulations with the DFT + U approach, systematically studying the dissociation dynamics and mechanism of water molecule and small clusters on the PuO 2 (110) surface. The dissociation of water on the surface is found to be a two-step hydroxylation process for both monomer and clusters, but different dissociation mechanisms are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Interfacial phenomena, such as photocatalytic water splitting, heterogeneous catalysis, electrochemistry, and surface adsorption, show that water can react with the active sites on the solid surface . Surface active sites can be hydrated by hydroxyls or water molecules. The presence of hydration layer on the surface treated/untreated by metal ions usually has a strong influence on the adsorption of collectors. , The adsorption of flotation reagents on the metal-ion-activated surface is usually stronger than that on the hydrated surface. , However, in flotation systems, hydration and dehydration of water/oxide–mineral interfaces, especially in the presence of activated ions, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial phenomena, such as photocatalytic water splitting, heterogeneous catalysis, electrochemistry, and surface adsorption, show that water can react with the active sites on the solid surface . Surface active sites can be hydrated by hydroxyls or water molecules. The presence of hydration layer on the surface treated/untreated by metal ions usually has a strong influence on the adsorption of collectors. , The adsorption of flotation reagents on the metal-ion-activated surface is usually stronger than that on the hydrated surface. , However, in flotation systems, hydration and dehydration of water/oxide–mineral interfaces, especially in the presence of activated ions, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the dissociative adsorption of H2O is feasible for a large range of temperature and water partial pressures on UO2 (111) surface [69]. The dissociation of H2O on PuO2 (110) surface is a two-step hydroxylation process both for single H2O molecule and H2O clusters [70]. The dissociation is initiated by the [70].…”
Section: Adsorption and Dissociation Of H 2 O On Ano 2 Surfacesmentioning
confidence: 99%
“…The dissociation of H2O on PuO2 (110) surface is a two-step hydroxylation process both for single H2O molecule and H2O clusters [70]. The dissociation is initiated by the [70]. The dissociation is initiated by the dehydrogenation of water molecules to form a hydroxyl group with surface oxygen atom, followed by successive surface hydroxylation on plutonium with the remaining hydroxide ion of the dissociating molecule.…”
Section: Adsorption and Dissociation Of H 2 O On Ano 2 Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plutonium is one of the main materials used in nuclear applications, and considerable experimental and theoretical efforts have been devoted to studying the structures and properties of elementary plutonium as well as its compounds [1][2][3][4][5]. For the safety of long-term storage of plutonium, a series of reactions may be involved, such as Pu [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%